Theological Review of Emotional Intelligence for Educators - Novia Purnomo (Diligentia: Journal of Theology and Christian Education, 2020)
Being a teacher is a rewarding yet challenging and demanding profession. Educators have complex roles because beside teaching knowledge, they must develop students’ skills (creativity, critical thinking, communication, and collaboration), attitudes, and values for work, citizenship, and life in the 21st century.  In the 21st century, educators who are expected to be role models for students must develop their emotional skills. Different studies have showed that the key to success is not just cognitive intelligence, rather 80% of success in life depends on emotional intelligence.[1] Emotional intelligence is evaluated as an important, valuable, and potential personal resource for coping with threats, challenges, and organizational setting related to tasks where emotional skill is required for successful performance such as school teaching. 4 competencies of emotional intelligence are self-awareness, self-management, social awareness, and relationship management. This paper aims at analyzing whether emotional intelligence is coherent to biblical concepts.  Discussion will be started by analyzing presuppositions of emotional intelligence which have been used by scholars, then reviewing and reconstructing emotional intelligence theologically to keep it aligned with biblical truth.